(Teaching) Regional Geography Proceedings of 27th Central European Conference. 17th October 2019, Brno - Mísařová, Darina; Petráková, Jana (Masaryk University Press, 2020)
The proceedings are the output of the 27th edition of the Central European Conference with subtitle (Teaching) of regional geography. The proceedings contain 19 contributions. Contributions indicate the current state of professional interest of conference participants. The contributions present current trends in geographical research by experts from the Czech Republic, Slovakia and Poland.